2019
DOI: 10.17509/mimbar-sd.v6i2.17562
|View full text |Cite
|
Sign up to set email alerts
|

Effect of STEM-based Learning on the Cognitive Skills Improvement

Abstract: The success in the modern era is determined by how students strive to have certain skills. This can be achieved by students through the development of cognitive domain, because it is considered as the ability to master subject matter with regard to thinking ability in addition to learning. Hence, this research aims at improving the learning outcomes in the cognitive domain of students at the primary school level. This research was conducted using the Pre-Experiment method with the pretest-posttest One-Group de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
(1 reference statement)
0
13
0
Order By: Relevance
“…So, the need for STEM programs and for preparing STEM educators is clear. Especially, when STEM education programs proved their effectiveness on developing students' cognitive, affective, and psychomotor abilities (Firdaus & Rahayu, 2019), as well as on student attitudes toward STEM in general, and toward STEM careers in particular (Guzey, Harwell & Moore, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…So, the need for STEM programs and for preparing STEM educators is clear. Especially, when STEM education programs proved their effectiveness on developing students' cognitive, affective, and psychomotor abilities (Firdaus & Rahayu, 2019), as well as on student attitudes toward STEM in general, and toward STEM careers in particular (Guzey, Harwell & Moore, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The STEAM application in learning activities is considered effective since STEM has an effective way to engage students in higher-order thinking and improve problem-solving skills by placing science and mathematics in the context of technology and engineering (Firdaus & Rahayu, 2019). STEAM can also collaborate with the ability of teachers, i.e., TPACK.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research was carried out by Kamienski & Radziwill (2018), who found that the STEAM learning approach could foster a new ability model that demonstrated empathy and increased student curiosity. Further relevant research was performed by Firdaus & Rahayu (2019), who concluded that TPACK is the knowledge needed to integrate technology into learning. Three components of teacher knowledge were produced: pedagogical content knowledge, technological content knowledge, and technological pedagogical knowledge.…”
Section: Related Researchmentioning
confidence: 99%
“…According to studies stem-based learning could improve cognitive and affective skills. The success in the modern era is determined by how students strive to have certain skills; and this can be achieved by students through the development of cognitive domain (Firdaus & Rahayu, 2019) In the study (Sutaphan & Yuenyong, 2018)…”
Section: 6%mentioning
confidence: 99%